AGRICULTURE FEED CHAPTER THE BASICS OF CROP IRRIGATION (Academicia Globe: Inderscience Research, 2022)
Crop is considered the most valuable, high – yield grain crop food, fodder, technical and agrotechnical importance. As food, cornstarch's Dogi is used. His Dogi is considered very nutritious and has an average content of 10,6% cutlet, 1,4% ash substances. But, in corn grain, the protein content is low. For this reason, bread is closed by adding 25-30% bug'doy flour to the corn flour. Since corn Dogi has a lot of precipitation (4,3-5,0%) in its composition, it quickly hurts it. Grain porridge is separated in special machines, flour is prepared from the rest, because in the composition of corn porridge contains about 25 – 40% fat, from which the oil used for food is prepared. In addition, cereals from corn cereals are prepared, during the milk – wax ripening period, it can be used as food, in which it is fried (tonsils) and boiled.